Draft Genome Sequence of Klebsiella pneumoniae UMB8492, Isolated from the Female Urinary Tract - Gondi, Suma (Microbiol Resour Announc, 2020)
Here, we present the draft genome sequence for Klebsiella pneumoniae strain UMB8492, isolated from a urine sample from a female patient with overactive bladder (OAB) symptoms. The assembled genome has a length of 5,660,575 bp, a G+C content of 57.19%, and an N(50) value of 136,315 bp.